Conceptual river water quality model with flexible model structure. (June 2018) - Nguyen, Thanh Thuy; Keupers, Ingrid; Willems, Patrick
Abstract: Physically-based river water quality models are valuable tools for river basin management and planning. However, their long computational times pose many difficulties for applications that involve a large number of model iterations. This paper addresses this problem by developing a faster, surrogate conceptual model based on the detailed reference models. The hydrodynamic information and water quality process equations from different detailed models are considered as ensembles in the developed model. The model conceptualizes rivers using cascades of reservoirs and lumps the advection-diffusion and physico-biochemical processes. We tested the model by comparing its performance for the Molse Neet river, Belgium, with two popular reference models, namely, MIKE 11 and InfoWorks RS. Results show that the conceptual model performs equally well as the reference models, but with simulation time 10 4 times faster. The successful testing of this model opens a development avenue towards problem solving in the context of water quality control and management. Highlights: Fast conceptual model for river water quality (CORIWAQ) developed. Flexible model structure based on MIKE11 ECO Lab and InfoWorks RS. CORIWAQ has similar performance as more detailed physically-based models with simulation times 10 4 times faster. CORIWAQ is qualified to implement further studies on scenario impact and uncertainty analysis and optimization.